Analysis of the impact of financial inclusion and FinTech on youth labour force participation in the MENA region - Elmasmari Hanane; Amaghouss Jabrane (Economics and Business Review)
This study examines the determinants of financial inclusion and FinTech, and then evaluates their effects on youth labour force participation in the MENA region. The World Bank’s Global Findex 2021 database was used to perform probit estimations and propensity score matching. The results show that young people with higher education levels, higher incomes, mobile phones and Internet access are more likely to be included in the traditional and digital financial systems. In addition, barriers to financial inclusion encompass a lack of documentation, religious constraints and the costs associated with financial services. Furthermore, examining the effect of financial inclusion and FinTech reveals that having formal bank accounts and mobile money accounts, as well as savings, formal loans, and digital transactions, has a significant impact on young people’s participation in the labour force.